2010
DOI: 10.1007/s00410-010-0489-z
|View full text |Cite
|
Sign up to set email alerts
|

Relative contributions of crust and mantle to generation of Campanian high-K calc-alkaline I-type granitoids in a subduction setting, with special reference to the Harşit Pluton, Eastern Turkey

Abstract: We present elemental and Sr-Nd-Pb isotopic data for the magmatic suite (*79 Ma) of the Harşit pluton, from the Eastern Pontides (NE Turkey), with the aim of determining its magma source and geodynamic evolution. The pluton comprises granite, granodiorite, tonalite and minor diorite (SiO 2 = 59.43-76.95 wt%), with only minor gabbroic diorite mafic microgranular enclaves in composition (SiO 2 = 54.95-56.32 wt%), and exhibits low Mg# (\46). All samples show a high-K calc-alkaline differentiation trend and I-type … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
83
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 150 publications
(90 citation statements)
references
References 97 publications
5
83
0
Order By: Relevance
“…The Upper Cretaceous sequences of the northern Eastern Pontides are composed mainly of back-arc volcaniclastics (Şengör and Yılmaz 1981;Okay and Şahintürk 1997;Okay and Tüysüz 1999;Dokuz and Tanyolu 2006;Topuz et al 2007;Karslı et al 2010) (Text-figs 1 and 2). These are deposits related to the closure of the northern branch of the Neotethys Ocean and northward subduction of its oceanic crust (Şengör and Yılmaz 1981;Okay and Şahintürk 1997;Yılmaz et al 1997;Okay and Tüysüz 1999;Şengör et al 2003;Çinku et al 2010;Karslı et al 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Upper Cretaceous sequences of the northern Eastern Pontides are composed mainly of back-arc volcaniclastics (Şengör and Yılmaz 1981;Okay and Şahintürk 1997;Okay and Tüysüz 1999;Dokuz and Tanyolu 2006;Topuz et al 2007;Karslı et al 2010) (Text-figs 1 and 2). These are deposits related to the closure of the northern branch of the Neotethys Ocean and northward subduction of its oceanic crust (Şengör and Yılmaz 1981;Okay and Şahintürk 1997;Yılmaz et al 1997;Okay and Tüysüz 1999;Şengör et al 2003;Çinku et al 2010;Karslı et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…These are deposits related to the closure of the northern branch of the Neotethys Ocean and northward subduction of its oceanic crust (Şengör and Yılmaz 1981;Okay and Şahintürk 1997;Yılmaz et al 1997;Okay and Tüysüz 1999;Şengör et al 2003;Çinku et al 2010;Karslı et al 2010). The volcaniclastics are followed by a calciclastics-dominated sedimentary sequence (Text- fig.…”
Section: Introductionmentioning
confidence: 99%
“…Several researchers suggested that the eastern Pontides was a magmatic arc that occurred as a result of northward subduction of the Neotethys along the southern border of the Sakarya Zone Karsli et al, 2010;Şengör & Yılmaz, 1981;Şengör et al, 2003;Ustaomer & Robertson, 2010;Yilmaz et al, 1997). Conversely, Dewey et al (1973), Bektaş et al (1999), Eyuboglu, Chung, et al (2011), and Eyuboglu, Santosh, et al (2011)proposed a southward subduction that continued uninterruptedly from the Paleozoic period until the end of the Eocene period.…”
Section: Geodynamic Implications and Magma Chamber Processesmentioning
confidence: 99%
“…Previous studies provided certain geochronological and geochemical constraints on the origin and evolution of Late Cretaceous magmatism. The geochemical nature of the great majority of Late Cretaceous magmatism is of calc-alkaline (Aydin, 2014;Ercan & Gedik, 1983;Karsli et al, 2010;Kaygusuz & Aydınçakır, 2009, 2011Tokel, 1983). However, rare volcanic and plutonic bodies, such as those in this study, attained high-K to shoshonitic composition Asan, Kurt, Francis, & Morgan, 2014;Bektas & Gedik, 1988;Eyüboğlu, 2010;Genç et al, 2014;Gülmez & Genc, 2015;Karsli et al, 2012;Varol, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The growth and reworking of continental crust is commonly triggered by the underplating of mantle magmas (Chen and Arakawa, 2005;Jahn et al, 2004). In subdution zones, the mantle rocks and the coeval granites have therefore recorded abundant information regarding the crustal growth and differentiation of continental crust (Kamei et al, 2004;Karsli et al, 2010). However, the production of the subdution-related magmatic rocks was always attributed to distinct dynamic mechanisms, including slab break-off (Davies and von Blanckenburg, 1995), ridge subduction (Abratis and Worner, 2001;Guivel et al, 1999), slab tearing (Guivel et al, 2006;Pallares et al, 2007), or slab roll-back (Kay and Mpodozis, 2001;Ramos and Folguera, 2009).…”
Section: Introductionmentioning
confidence: 99%